Structural Control With Control-Engineering-Based Methods - Miyamoto, Kou; Chen, Yinli; Sato, Daiki; She, Jinhua (Reference Module in Materials Science and Materials Engineering, 2015)
This chapter describes structural control methods utilizing control engineering techniques. It explores passive, semi-active, and active control devices and their applications in suppressing earthquakes and wind-induced vibrations. Section “Typical Structural-control Devices” describes typical structural control devices from a control-engineering perspective, as well as the theoretical foundations and practical applications of structural control. The most commonly use devices are tuned mass dampers (TMDs) and active TMDs (ATMDs). Related technologies and control methods are explained for them throughout the chapter. Section “Active and Semi-Active Control for Earthquakes” explains and demonstrates structural control devices and systems of active and semi-active control for seismic protection. Several semi-active control studies have validated the effectiveness of the methods using large shaking tables and test specimens. Section “Vibration Control for Wind-induced Vibrations” describes studies of wind-induced vibration suppression. Control methods, including LQR, LQG, H∞, and sliding-mode control (SMC), are applied to TMDs, TMD-like dampers, and other devices. Section “Conclusion” summarizes the main points in the chapter and presents some concluding remarks.